Expectant Management of a Triploid Partial Molar Pregnancy at 26 Weeks' Gestation: A Case Report - Wong, Karen; Ali, Mohannad; Stalder, Marc; Bonin, Brigitte; El-Chaâr, Darine (American Journal of Perinatology Reports, 2024)
Introduction Triploid partial molar pregnancies are not viable, and confer maternal risks including preeclampsia, hemorrhage, gestational trophoblastic neoplasia, and trophoblastic embolization. We report a case managed expectantly until 26 weeks' gestation in a patient requesting continuation of pregnancy.Case Presentation This G2P1 presented with fetal anomalies indicative of triploid partial molar pregnancy. The pregnancy was complicated by anemia, hyperthyroidism, supraventricular tachycardia, and threatened preterm labor.Her care involved maternal fetal medicine collaborating with internal medicine, palliative care, anesthesia and critical care. Labor was augmented at 26 weeks' gestation, resulting in vaginal delivery. Postpartum course was notably complicated by acute respiratory distress in the immediate postpartum period, which self-resolved. Postpartum hemorrhage and retained products of conception were additional complications.Conclusion This unique case highlights the role of multidisciplinary collaboration and shared decision making in challenging circumstances.
Keywords: triploidy; partial molar; perinatal palliative care; gestational trophoblastic neoplasia